2011
DOI: 10.3109/10641963.2010.549266
|View full text |Cite
|
Sign up to set email alerts
|

Consequence of Masked Hypertension in Treated Hypertensive Outpatients: 1-Year Follow-Up Study

Abstract: Since masked hypertension (MHT) is high risk for cardiovascular disease, the importance of home blood pressure (HBP) control is emphasized. The aim of this study was to investigate the prevalence of MHT in the treated hypertensives and the consequence of their BP control status after a 1-year follow up period. Subjects are 262 treated hypertensive outpatients. We assessed BP control status, background characteristics, and antihypertensive drugs in both 2008 and 2009. Clinic BP (CBP) and morning HBP in 2008 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Among the included studies, 22 studies contained both home morning and evening BP values, 6 , 7 , 8 , 9 , 10 , 11 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 whereas 13 studies contained only home morning BP values. 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 10 studies were conducted in European countries. 6 , 7 , 8 , 15 , 16 , 17 , 18 , 19 , 22 , 25 whereas 25 studies were conducted in Asian countries 9 , 10 , 11 , 20 , 21 , 23 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included studies, 22 studies contained both home morning and evening BP values, 6 , 7 , 8 , 9 , 10 , 11 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 whereas 13 studies contained only home morning BP values. 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 10 studies were conducted in European countries. 6 , 7 , 8 , 15 , 16 , 17 , 18 , 19 , 22 , 25 whereas 25 studies were conducted in Asian countries 9 , 10 , 11 , 20 , 21 , 23 , …”
Section: Resultsmentioning
confidence: 99%
“… 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 10 studies were conducted in European countries. 6 , 7 , 8 , 15 , 16 , 17 , 18 , 19 , 22 , 25 whereas 25 studies were conducted in Asian countries 9 , 10 , 11 , 20 , 21 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 (22 in Japan). 9 , 10 , 11 , 20 , 21 ,…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that patients with metabolic syndrome show higher urinary salt excretion and need more antihypertensive drugs to manage their BP (17). Habitual drinking, male gender and older age are also reported to associate with persistently uncontrolled home BP (2,18). Since marked BP reduction can be achieved by a combination of salt restriction, weight loss, exercise, restriction of alcohol intake, and a DASH diet (19), comprehensive lifestyle modifications seem to be important for achieving BP control in hypertensive patients, in particular, young male patients with obesity.…”
Section: Discussionmentioning
confidence: 98%
“…Blood pressure (BP) control was reported to be inadequate on the basis of either the routine clinic BP or home BP measurement (1)(2)(3). The Japanese Society of Hypertension guideline (JSH 2009) emphasizes that the use of two or three drugs including a low dose of diuretic is necessary to achieve the target BP (4).…”
Section: Introductionmentioning
confidence: 99%
“…These include male gender, alcohol consumption, obesity, smoking, physical activity, and psychosocial factors such as anxiety, interpersonal conflicts and job stress. 18 There was no significant difference in age between patients with MH and patients with SH or WCH, however, age was significantly higher in MH than true normotensive patients. There was no significant difference in sex incidence between patients with MH and patients with SH or true normotensive patients, however, male sex was significantly higher in MH than WCH.…”
Section: Discussionmentioning
confidence: 78%